2011
DOI: 10.1063/1.3669391
|View full text |Cite
|
Sign up to set email alerts
|

Thermal tuning of Lamb wave band structure in a two-dimensional phononic crystal plate

Abstract: Using supercell-plane-wave-expansion method, we have made a theoretical study of the temperature effects on the band structure of Lamb wave in a two-dimensional phononic crystal plate. The numerical results show that the Lamb wave bandgap is very sensitive to temperature. For the case of Ba0.7Sr0.3TiO3/epoxy phononic crystal, the width of bandgap becomes narrower in a hexagonal lattice system as the temperature increases, but it becomes wider in a phononic crystal plate with square lattice. On the other hand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 21 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…One way to address this engineering challenge is to develop a structure whose properties adapt to external conditions such as deformation, applied load, applied temperature, and/or humidity. This concept of tunable metamaterials or phononic crystals has been explored in recent literature using deformations [7][8][9], applied loads [10], temperature-sensitive materials [11][12][13][14][15], topological transformation of structures [16][17][18], applied voltage to control the thickness and tension in elastomers [19,20], magneto-granular materials [21] and magnetoelastic mate-rials [22,23]. While prior work has shown the ability to open, close, and generally tune band gaps with a variety of mechanisms, we instead focus on a method to tune the band gaps in a specified direction by analyzing the mode shapes of the meta-structure, given the ability to tune the modulus of the meta-structure constituents with an applied temperature.…”
Section: Introductionmentioning
confidence: 99%
“…One way to address this engineering challenge is to develop a structure whose properties adapt to external conditions such as deformation, applied load, applied temperature, and/or humidity. This concept of tunable metamaterials or phononic crystals has been explored in recent literature using deformations [7][8][9], applied loads [10], temperature-sensitive materials [11][12][13][14][15], topological transformation of structures [16][17][18], applied voltage to control the thickness and tension in elastomers [19,20], magneto-granular materials [21] and magnetoelastic mate-rials [22,23]. While prior work has shown the ability to open, close, and generally tune band gaps with a variety of mechanisms, we instead focus on a method to tune the band gaps in a specified direction by analyzing the mode shapes of the meta-structure, given the ability to tune the modulus of the meta-structure constituents with an applied temperature.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent these difficulties, filters and wave guides had previously been developed to isolate specific modes of the Lamb wave [6,7], as well as to confine the wave propagation to specific directions [8]. The strategies for mode isolation revolve mainly around the use of phononic crystals, which prevents the transmission of selective wave frequencies through the action of Bragg scattering [9][10][11][12][13][14][15][16][17][18][19][20][21]. To achieve unidirectional transmission, on the other hand, requires breaking either the spatial inversion symmetry or the time-reversal symmetry [22].…”
Section: Introductionmentioning
confidence: 99%
“…Tuning and switching the hypersonic phononic properties is realized through phase transitions of crystallization and melting, which can be tuned by temperature [15]. Recently, it was suggested that ferroelectric ceramics are suitable for tunable PC, since their acoustic velocities are sensitive to the temperature across Curie temperature (T C ) [18][19][20][21]. Nevertheless, most of these studies were theoretical in nature, and focused on the obvious effects of external stimuli on the band structure of an infinite PC.…”
Section: Introductionmentioning
confidence: 99%